Barrier‐induced supershear ruptures on a slip‐weakening fault. Issue 12 (25th June 2015) - Weng, Huihui; Huang, Jinshui; Yang, Hongfeng
Abstract Here we investigate the effects of a patch with elevated effective normal stress (barrier) on two‐dimensional in‐plane supershear rupture propagation on a planar fault from numerical experiments. Our results confirm that the barrier may slow down or stop coseismic ruptures but may also induce supershear ruptures. We demonstrate that the supershear rupture may emerge in a region that is delineated by two approximate linear boundaries. If the barrier size is below the lower boundary, ruptures can overcome the barrier and propagate at subshear speeds. If the barrier size is larger than the upper boundary, ruptures are always stopped by the barrier. Furthermore, we find that the barrier‐induced supershear ruptures may eventually slow down into subshear speed, depending on the size and the location of the barrier. The duration of supershear ruptures increases as the barrier sizes grow from the lower to the upper boundary, which are proportional to the reduction in rupture speeds caused by the barrier. These results indicate that a barrier on the fault may not stop coseismic ruptures. Rather, the barrier may induce ruptures propagating at supershear speeds that play important roles in near‐field ground shaking and damage.